WORKSHOP SELF AWARENESS SEBAGAI LANGKAH PERSIAPAN DIRI DALAM DUNIA KERJA PADA SISWA SMK SMTI MAKASSAR - St. Hadjar Nurul Istiqamah; Moh. Fachri Zahdy, A. Zhafirah Anisa Putri, A. Fraya Sashikirana A. F. (Adiba Aisha Amira, 2022)
The need for sufficient human resources in the industrial world is of great concern, especially for individuals who are involved in the industrial world, including at the level of education directly supervised by the agency or ministry of manpower with an orientation towards the world of industrial work. The purpose of this research is to provide students with provisions related to self-awareness in order to make it easier for students to know themselves and future goals for career preparation in the world of work. This study uses the psychoeducational method by presenting experts as presenters to provide additional knowledge related to self-awareness. The result of this psychoeducation is that students get additional knowledge in the form of the importance of self-awareness, supporting and inhibiting factors, what benefits can be obtained by cultivating a sense of self-awareness, as well as tips for increasing self-awareness. 95% of the 193 participants were satisfied with the self-awareness psychoeducation (workshop).